2022
DOI: 10.1007/s12560-022-09509-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Disinfectants Suitable for Inactivating SARS-CoV-2 at Cold-Chain Temperature

Abstract: To prevent the spread of SARS-CoV-2 in cold-chain transportation in China, we developed specific cryogenic disinfectants. Carrier tests were performed against SARS-CoV-2 at − 20 °C for the four cryogenic disinfectants developed and qRT-PCR was used to test the virus RNA. Peracetic acid, chlorine disinfectants (two different concentrations), and quaternary ammonium disinfectant with their antifreeze can all inactivate SARS-CoV-2 in 5 min at − 20 °C. However, after 2–3 h of exposure, only chlorine disinfectant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
(14 reference statements)
1
10
0
Order By: Relevance
“…Moreover, we anticipate the POA-inactivated viruses to remain detectable by RT-qPCR methods, which has already been reported for surface disinfection of SARS-CoV-2 by PAA. 68 Contrary to POAs, free chlorine led to a significant genome loss with normalized rate constants (k normalized , eqs 1 and 2) at 4.55 and 0.35 L•mg −1 •s −1 •base −1 , for MS2 and Φ6, respectively, which are comparable with previous publications (Figure 5c). 36,39,69,70 The k normalized for the enveloped Φ6 was significantly lower than that of the nonenveloped MS2, which could be ascribed to the stability of dsRNA relative to ssRNA, or the shielding effect of the glycerophospholipid envelope.…”
Section: Inactivation Of Viruses In Phosphatesupporting
confidence: 88%
“…Moreover, we anticipate the POA-inactivated viruses to remain detectable by RT-qPCR methods, which has already been reported for surface disinfection of SARS-CoV-2 by PAA. 68 Contrary to POAs, free chlorine led to a significant genome loss with normalized rate constants (k normalized , eqs 1 and 2) at 4.55 and 0.35 L•mg −1 •s −1 •base −1 , for MS2 and Φ6, respectively, which are comparable with previous publications (Figure 5c). 36,39,69,70 The k normalized for the enveloped Φ6 was significantly lower than that of the nonenveloped MS2, which could be ascribed to the stability of dsRNA relative to ssRNA, or the shielding effect of the glycerophospholipid envelope.…”
Section: Inactivation Of Viruses In Phosphatesupporting
confidence: 88%
“…The residue of commonly used disinfectants will have a certain impact on food or people ( Choi et al., 2018 ; Wu et al., 2022 ), and it is difficult to ensure safety when applied to cold-chain disinfection. Researchers have indicated that UV light, sunlight, 405 nm visible light, and 400 nm-to-420 nm standard LED light effectively inactivate SARS-CoV-2 at 20°C ( Heilingloh et al., 2020 ; Ratnesar-Shumate et al., 2020 ; Rathnasinghe et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the method commonly used to disinfect the surface of items is ultraviolet (UV) radiation or sprayed disinfectant containing sodium hypochlorite, peroxyacetic acid, or benzalkonium chlorides. Common disinfectants, including sodium hypochlorite and peroxyacetic acid, can be easily frozen after being sprayed under the cold-chain environment, resulting in a sharp decline in disinfection efficacy ( Wu et al., 2022 ). In addition, a study indicated that the residual disinfectant may also be potentially harmful to personnel in subsequent contact ( Choi et al., 2018 ; Li et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Peracetic acid (blended with ethanol), chlorine disinfectant (trichloroisocyanuric acid, blended with ethylene glycol) with two concentrations, and quaternary ammonium salt (DNC, blended with ethanol) can inactivate SARS-CoV-2 on the cold chain's surface. The RNA of SARS-CoV-2 remained detectable in 2-3 h disinfection, even if disinfectants fully inactivated the virus in 5 min (Wu et al, 2022). Gautret and coworkers (2020) suggested that public spitting in China may have played a significant role in encouraging the transmission of SARS-CoV-2.…”
Section: Improving Management Of Wastewater Treatment Facilitiesmentioning
confidence: 99%